Analisis nilai indeks keberlanjutan usaha tani hanjeli di Desa Waluran Mandiri Sukabumi dengan metode Raphanjeli - Kastana Sapanli; Nabila Nur Septiani; Sahaya Aulia Azzahra; Zulfani Rahmah Izzati Putri; Lailatun Nikmah; Izumi Risma Ayuka (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
Increasing local commodity-based food diversification programs is a solution to overcome dependence on rice imports and realize food self-sufficiency. One of the plants that have the potential as an alternative staple food is hanjeli. The purpose of this study was to analyze the level of sustainability of hanjeli integrated farming from the ecological, economic, social and technological dimensions. The data used were primary data through interviews and secondary data through literature studies. The data analysis method used Rapid Appraisal for Hanjeli (Raphanjeli) to determine the value of the sustainability index. The results showed that a sustainability index of 66.35 was obtained, which means it is quite sustainable. The strategy for improving the sustainability of hanjeli farming based on the results of leverage analysis is the need for the development of alternative employment opportunities, improving the quality of human resources and the existence of guidelines in the application of technology